A proposed English proficiency test in pronunciation for six Asian student groups - Cuevas, Soledad Landicho 1940- (1971)
This study presents an English proficiency test in pronunciation for Asian students who desire to enroll in the universities and colleges in the Philippines. The English test was constructed to measure the Asian students competence in the language with reference to the auditory perception and auditory comprehension skills required to cope with the communication situations to which the learner will be exposed. The findings of the study revealed that in general, the test items were of high discriminating power since they distinguish significantly the bright group and the poor group of examinees.